(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
It is known that Fitrat is a scientist who made a significant contribution to the development of the Uzbek language as a linguist. His works "Sarf" and "Nahv" were important scientific works on the grammar of the Uzbek language in their time and served as a guide for learners. This article highlights Fitrat’s views on linguistics and his views on agreement.